A Nanoscale Hot-Wire Flow Sensor Based on CMOS-MEMS Technology - Wang, Xiaoyi; Fang, Zetao; Song, Xiangyu; Xu, Wei (Frontiers in Mechanical Engineering, 2022)
In this paper, we proposed an ultrafast and nanoscale hot-wire flow (NHF) sensor implemented in a 0.18µm complementary metal-oxide-semiconductor microelectromechanical system (CMOS-MEMS) technology. An in-house developed post-CMOS fabrication process was leveraged to release the nanowires and reduce their thickness and width, thereby the heat conduction loss is greatly suppressed, while the response time of the NHF sensor is significantly improved. Benefiting from the nano size of the hot wire (a width of 622nm), the flow sensor exhibits an ultrafast response time of 30µs (@ airflow of 0m/s), a good detectable flow range of 0~30m/s, and a cut-off frequency of 21kHz under the constant temperature (CT) mode. In addition, an equivalent circuit model (ECM) was established in PSPICE to predict the NHF sensor performance, and the theoretical simulation results were in good agreement with the experiment results.